The public prosecutor and sentencing: drug trafficking and the death penalty in Singapore. (2nd January 2018) - Amirthalingam, Kumaralingam
ABSTRACT: The Public Prosecutor has a role to play in assisting the courts in sentencing. However, the extent of this role remains controversial with different jurisdictions drawing the line at different points. It is generally accepted that the Public Prosecutor, as a member of the Executive, should not be empowered to determine the sentence, as doing so would violate the doctrine of the separation of powers. This article examines the role of the Public Prosecutor in sentencing in the context of drug trafficking offences that carry the death penalty in Singapore. The Government has abolished the mandatory death penalty and replaced it with discretionary sentencing when certain conditions are met, one of which is that the Public Prosecutor has certified that the offender has rendered substantive assistance in disrupting drug trafficking activities. This discretionary power is largely protected from judicial review, raising an important constitutional question pertaining to the separation of powers.